PENGARUH PENERAPAN STRATEGI GENERATIVE LEARNING TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VIII SMP N 5 PARIAMAN - Kurniawan, Hendra - (STKIP PGRI Sumbar, 2014)
The research was due to the fact that studentsâ outcome in learning biology was considered to be low. Students learned inactively, the learning process was teacher-centered, and the student had lack of interaction. One possible way to copewith the problems was to implement Generative Learning Strategy during teaching and learning process. The research aimed and finding out influence of the implementation of Generative Learning strategy toward studentsâ biology learning outcomes at SMP N 5 Pariaman grade VIII. The design of the research was experimental research, using randomized control posttest only design. The population in the research was all grade VIII student of SMP N 5 Pariaman 2013/2014. The sample was chosen using purposive sampling technique. The sample of the research was 24 grade VIII2 student as the experiment group and 23 grade VIII5 students as the control group. The form of the test was multiple-choice test. The items were 34 questions. Based on the research findings, it was seen that exsperiment groupâs mean score was 78,79 while the control group obtained 73,90. From the data analysis, it was obtained that the tcalculated was 2,48 while the ttable was 1,67. Therefore, the tcal>ttable, which meant that the hypothesis was accepted, with the degree of certainty was 95% (Î±=0,05). It was concluded that Generative Learning strategy influenced positively toward studentsâ biology learning outcomesâ at grade VIII student of SMP N Pariaman 2013/2014.